(untitled) (Pedagogy of Higher and Secondary Education, 2012)
Sokolova S. V. A retrospective analysis of the origins of legal culture in pedagogical theory from the time of Kievan Rus to the second half of the nineteenth century. Analysis of legal culture origin in national pedagogical belief has been made. Significance of legal education in legal culture forming and legal awareness has been defined.